From Self-Esteem to Selflessness: An Evidence (Gap) Map of Self-Related Processes as Mechanisms of Mindfulness-Based Interventions - Britton, Willoughby B.; Desbordes, Gaëlle; Acabchuk, Rebecca; Peters, Sarah; Lindahl, Jared R.; Canby, Nicholas K.; Vago, David R.; Dumais, Travis; Lipsky, Jonah; Kimmel, Hannah; Sager, Lauren; Rahrig, Hadley; et al. (Frontiers in Psychology, 2021)
Self-related processes (SRPs) have been theorized as key mechanisms of mindfulness-based interventions (MBIs), but the evidence supporting these theories is currently unclear. This evidence map introduces a comprehensive framework for different types of SRPs, and how they are theorized to function as mechanisms of MBIs (target identification). The evidence map then assesses SRP target engagement by mindfulness training and the relationship between target engagement and outcomes (target validation). Discussion of the measurement of SRPs is also included. The most common SRPs measured and engaged by standard MBIs represented valenced evaluations of self-concept, including rumination, self-compassion, self-efficacy, and self-esteem. Rumination showed the strongest evidence as a mechanism for depression, with other physical and mental health outcomes also supported. Self-compassion showed consistent target engagement but was inconsistently related to improved outcomes. Decentering and interoception are emerging potential mechanisms, but their construct validity and different subcomponents are still in development. While some embodied self-specifying processes are being measured in cross-sectional and meditation induction studies, very few have been assessed in MBIs. The SRPs with the strongest mechanistic support represent positive and negative evaluations of self-concept. In sum, few SRPs have been measured in MBIs, and additional research using well-validated measures is needed to clarify their role as mechanisms.